Self‐Adapting Electrochemical Grinding Strategy for Stable Silicon Anode. (27th October 2021) - Wang, Haozheng; Man, Han; Yang, Jinghao; Zang, Jiahe; Che, Renchao; Wang, Fei; Sun, Dalin; Fang, Fang
Abstract: The pulverization of silicon during lithiation/delithiation due to its huge volume change results in a loss of electrochemical activity. In this work, advantage is taken of the unavoidable pulverization and an innovative strategy of in‐situ self‐adapting electrochemical grinding (ECG) is designed for stable silicon anode. MgH2 is utilized as the grinding aid to electrochemically grind micronsized Si particles. During ECG process, the lithiation processes of MgH2 and Si occur at different potentials and both result in appreciable volume expansion, leading to a strong internal stress inside the electrode. With this strong internal stress, the lithiation products of MgH2, i.e., Mg and LiH, would migrate into the cracked Si particles and gradually transform into a conductive matrix consisting of ionic conductive LiH and electronic conductive via partially reversible lithiation of Mg. After ECG process, micronsized Si particles are spontaneously grinded to an equilibrium size, which can accommodate the volume change and ensure the stable cycling. As prepared Si anode delivers an excellent reversible specific capacity of 3228 mAh g −1 and a capacity retention of 91% after 200 cycles. The proposed in situ self‐adapting ECG strategy offers a unique perspective for the development of Si‐based anode materials for next‐generation lithium ion batteries. Abstract : A self‐adapting electrochemical grinding (ECG) strategy is demonstrated for the preparation of stable silicon anode. By utilizing MgH2 as the grinding aid, micronsized Si particles are spontaneously grinded to an equilibrium size, which can accommodate the volume change and ensure the stable cycling. As prepared Si anode delivers an excellent reversible specific capacity.